Persistence of hepatitis B virus covalently closed circular DNA in hepatocytes: molecular mechanisms and clinical significance - Yang, Hung-Chih (Nature Publishing Group, 2014)
Covalently closed circular DNA (cccDNA) is the transcriptional template of hepatitis B virus (HBV). Extensive research over the past decades has unveiled the important role of cccDNA in the natural history and antiviral treatment of chronic HBV infection. cccDNA can persist in patients recovering from acute HBV infection for decades. This explains why HBV reactivation occasionally occurs in patients with resolved hepatitis B receiving intensive immunosuppressive agents. In addition, although advances in antiviral treatment dramatically improve the adverse outcomes of chronic hepatitis B (CHB), accumulating evidence demonstrates that current antiviral treatments alone, be they nucleos(t)ide analogs (NAs) or interferon (IFN), fail to cure most CHB patients because of the persistent cccDNA. NA suppresses HBV replication by directly inhibiting viral polymerase, while IFN enhances host immunity against HBV infection. Viral rebound often occurs after discontinuation of antiviral treatment. The loss of cccDNA can be induced by non-cytolytic destruction of cccDNA or immune-mediated killing of infected hepatocytes. It is known that NA has no direct effect on viral transcription or cccDNA stability. Therefore, the long half-life of hepatocytes leads to a very slow decline in cccDNA in patients under antiviral therapy. Novel antiviral agents targeting cccDNA or cccDNA-containing hepatocytes are thus required for curing chronic HBV infection.